The Sharia Marketing Strategy in Hospitals to Meet Customer Health Needs - Enrico Adhitya Rinaldi; Erlina Puspitaloka Mahadewi (International Journal of Science, Technology & Management, 2026)
The concept of sharia marketing in hospitals currently has differences with conventional marketing that invite customers to approach their Lord through health services. This new trend is not found in conventional marketing concepts. Hospitals play an important role in the development of public health, and the products or services produced are appropriate to meet customer needs, in health services that bring them closer to Allah the Creator with the maqoshid sharia approach. Customers whose needs are met will feel satisfied and their worship will be of increasing quality with better health conditions. The method in this writing is a study of sharia marketing literature by discussing marketing strategies in Islam that can be implemented in sharia and non-sharia hospitals (general hospitals) that want to apply it. Result: in several dimensions must meet the provisions of Islamic Sharia, including 1. products must be halal and have the right quantity and quality; 2. changing prices must be followed by changes in product quantity and quality and have price control; 3. Place can be interpreted as distribution and business premises should be able to create value and raise a better standard of living by providing ethical services; 4. promotional ethics avoid false and misleading advertising; 5. Marketers must be honest and responsible for the products they produce; 6. They must possess intellectual integrity and a higher level of awareness throughout the process; 7. Their physical business premises must have an Islamic architectural style; 8. They must be faithful in their promises; and 9. They must be patient in their service and communication. Decisions based on Sharia Marketing Strategies (SMS) are crucial for hospital management and marketers in carrying out their role as pioneers of Islamic outreach in hospital healthcare services.